2012
DOI: 10.1186/ar3796
|View full text |Cite
|
Sign up to set email alerts
|

Intimal lining layer macrophages but not synovial sublining macrophages display an IL-10 polarized-like phenotype in chronic synovitis

Abstract: IntroductionSynovial tissue macrophages play a key role in chronic inflammatory arthritis, but the contribution of different macrophage subsets in this process remains largely unknown. The main in vitro polarized macrophage subsets are classically (M1) and alternatively (M2) activated macrophages, the latter comprising interleukin (IL)-4 and IL-10 polarized cells. Here, we aimed to evaluate the polarization status of synovial macrophages in spondyloarthritis (SpA) and rheumatoid arthritis (RA).MethodsExpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 60 publications
4
98
0
1
Order By: Relevance
“…Histological analyses of biopsies showed that sublining macrophages had a heterogeneous phenotype because they co-expressed markers found on in vitro IFN-Îł-polarised, IL-4-polarised or IL-10-polarised cells. In contrast, intimal lining layer macrophages revealed a strong co-expression of CD163 and CD32, leading the authors to propose that intimal macrophages displayed an IL-10-polarised-like phenotype 37. Since our data have highlighted the phenotypic overlap between the IL-10-exposed and the M-CSF-exposed cells, it could alternatively be proposed that the expression of these two markers results from an exposure to M-CSF.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Histological analyses of biopsies showed that sublining macrophages had a heterogeneous phenotype because they co-expressed markers found on in vitro IFN-Îł-polarised, IL-4-polarised or IL-10-polarised cells. In contrast, intimal lining layer macrophages revealed a strong co-expression of CD163 and CD32, leading the authors to propose that intimal macrophages displayed an IL-10-polarised-like phenotype 37. Since our data have highlighted the phenotypic overlap between the IL-10-exposed and the M-CSF-exposed cells, it could alternatively be proposed that the expression of these two markers results from an exposure to M-CSF.…”
Section: Discussionmentioning
confidence: 55%
“…However, the idea that the M-CSF-induced macrophage phenotype is common in RA joints is sustained by strong circumstantial evidence. Indeed, despite the current difficulties, the use of the specific markers of human macrophages described by Ambarus et al 29 has allowed a preliminary appraisal of the polarisation status of synovial macrophages in RA and spondyloarthritis 37. Histological analyses of biopsies showed that sublining macrophages had a heterogeneous phenotype because they co-expressed markers found on in vitro IFN-Îł-polarised, IL-4-polarised or IL-10-polarised cells.…”
Section: Discussionmentioning
confidence: 99%
“…2A–F). The presence of immunomodulatory cytokines and other factors in tissue can impact on gene expression and subsequent macrophage functional responses, a process referred to as polarization, and it has previously been shown that ST macrophages in inflammatory arthritis are phenotypically heterogeneous [41]. To determine which subtypes of macrophages express PRLR, we differentiated healthy donor monocytes under various polarizing conditions, including GM-CSF, IFN-Îł, IL-10, M-CSF and RA SF.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, when they accumulate in tissues, where they are notably met by macrophages endowed with a higher capacity of cytokine response, they are more likely to cause inflammation and the extra-articular manifestations to which they are associated 37. However, it should be stressed that our study only investigated the response of M-CSF-differentiated macrophages, taken as prototypic synovial tissue macrophages38 39 while macrophages can be phenotypically and functionally heterogeneous,40 and recent data suggest that different subpopulations of macrophages with different FcÎł receptor expression profiles coexist in the RA synovial membrane 41 42. It would therefore be interesting to compare the cytokine responses of differentially polarised macrophages to ACPA-IC.…”
Section: Discussionmentioning
confidence: 98%